Dangerous Implication Of Takfir - Agam Royana (UIN Mataram, 2021)
Faith is a fundamental principle in religion. It is the foundation of belief in living which is based on God's rules. In Islam faith is an initial unitary step in undergoing worship which is called the pillars of faith. They are belief in Allah SWT, angels, scriptures, prophets, afterlife, and in the good and bad conditions which are had by His servants. However, in modernity and the treasures of Islam, Islam seems to be a late religion to be born. By reviving the strong desire in the golden era of the Salaf al-Salih, but with a textual understanding and regardless of the historical context. Some people are not aware that time is changing, dynamic and developing, but Islam tends to be an exclusive, old-fashioned and not in line with modernity. A textual understanding emerges too much religious believers which had been reproached by previous believers. In fact, the Qur'an has presented testimony in its diction, reminded its people not to be too much, strict and radical. The Messenger of Allah himself in his sunnah forbade his fellow to be too much in practicing Islam, spend all night in worship and tahajjud, or fast all day or even not get married. The phenomenon of over-practicing in religion cannot be underestimated, especially in this age of pluralism. Rigidity, and self-righteousness and even labeling other groups having different views as kafir or unbelievers really have negative effects, impacts and consequences. No wonder these dynamics make Moslems dichotomous and splitted, even easily played to fight against each other. This journal tries to present how much the effect, impact and bad consequences on the label of kafir on other Moslems. The researcher hopes to reduce people's carelessness on labeling other Moslems as kafir.",